Predictors of Anaemia Prevalence Among Ghanaian Pregnant Women: A Cross-Sectional Study - Jones Asafo Akowuah; Ebenezer Owusu-Addo; Ama Antwiwaa Opuni (SAGE Publishing, 2022)
Anaemia during pregnancy is a major public health concern. Despite its wide scope and adverse effects including increased maternal and perinatal morbidity and mortality, and long-term adverse effects on the newborn, appropriate interventions using upstream approaches to public health have largely not been implemented. This study investigated the prevalence and associated factors of anaemia among pregnant women in four health facilities in the Kwabre East Municipality. A cross-sectional survey with a two-stage sampling technique was conducted on 220 pregnant women who attended antenatal care at the selected health facilities. Interview-based structured questionnaires were used. Bivariate and multivariate logistic regression were used to identify predictors. The prevalence of anaemia was 11.4%. Few women (25) were anaemic and morphologically, 14 (56%) had normocytic normochromic anaemia and 9 (36%) had microcytic hypochromic anaemia. Iron deficiency was reported in 19 (8.6%) pregnant women. Independent predictors of anaemia were iron sulphate intake (AOR [95% CI] = 3.16 [1.15, 7.37], ANC follow-up during pregnancy (AOR [95% CI] = 3.07 [1.59, 7.99], household size of ≥5 (AOR [95% CI] = 3.58 [1.75, 9.52], folic acid intake (AOR [95% CI] = 5.29 [2.65, 12.39] and the period in pregnancy AOR [95% CI] = ≥36 weeks 3.2 (1.3-4.5). Though anaemia prevalence has been low in urban areas as previously reported, collaborated healthcare measures that aim at eradicating the menace are encouraged. Maternal healthcare interventions including the administration of folic acid, regular iron sulphate intake and intensive education on early ANC are recommended.